The Effect of the Discovery Learning Model Assisted by Mind Mapping on Students' Metacognition Ability - Kesumawardani, Aryani Dwi; Wati, Cindy Ira; Sari, Aulia Novita; Fiani, Raicha Okta; Wati, Eka Rina; Sawitri, Endang (Biosfer: Jurnal Tadris Biologi, 2024)
This study aims to determine the influence of the Discovery Learning model assisted by Mind Mapping on students' metacognition ability in Biology subjects. This study is a quantitative research with a quasi-experimental design. The sampling method employed was the cluster random sampling technique. The data collection techniques were the test and questionnaires. The data analysis techniques used were the t-test and N-Gain test. The t-test obtained a significance value (sig) of 0.000 > 0.05 (less than 0.05). It means that H1 was accepted and H0 was rejected. Based on the average N-Gain scores, the test and questionnaire results indicated that metacognitive ability was higher in the experimental class (60.58) with an "effective" category and 45.50 with a "moderately effective" category, compared to the control class (26.89) with an "ineffective" category and 30.94 with a "less effective" category. These findings demonstrate that the Discovery Learning model, assisted by Mind Mapping, significantly enhances the metacognitive abilities of Senior high school students.ABSTRAK: Penelitian ini bertujuan untuk mengetahui pengaruh model pembelajaran Discovery Learning berbantuan Mind Mapping terhadap kemampuan metakognisi peserta didik pada mata pelajaran Biologi. Penelitian ini merupakan jenis penelitian kuantitatif dengan menggunakan metode kuasi eksperimen dan pengambilan dengan teknik Cluster Random Sampling. Teknik pengumpulan data berupa soal tes dan angket. Teknik analisis data yang digunakan adalah Uji t-Test dan N-Gain. Hasil uji t-Test diperoleh nilai signifikansi (sig) yaitu  0,000 > 0,05 (lebih kecil dari 0,05) yang berarti H1 diterima dan H0 ditolak. Berdasarkan hasil nilai rata-rata N-Gain hasil tes dan angket Kemampuan metakognitif lebih tinggi di kelas eksperimen sebesar 60,58 dengan kategori efektif dan sebesar 45,50 dengan kategori cukup efektif dibandingkan dengan kelas kontrol yaitu 26,89 dengan kategori tidak efektif dan 30,94 dengan kategori kurang efektif. Hasil ini menunjukkan bahwa pengaruh model pembelajaran Discovery Learning berbantuan Mind Mapping secara signifikan mempengaruhi kemampuan metakognisi siswa SMA.